The acceptance of SARS‐CoV‐2 rapid antigen self‐testing: A cross‐sectional study in China. Issue 1 (25th October 2022) - Wu, Fan; Yuan, Yue; Li, Yanjun; Yin, Di; Lang, Bing; Zhao, Yangguo; Fan, Xueying; Zou, Huachun; Zhang, Chunhuan; Zeng, Xiangyue; Sun, Caijun
Abstract: Compared with the nucleic acid amplification test (NATT), the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) rapid antigen self‐testing (RAST) has advantages in speed and convenience. However, little is known about people's acceptance and influencing factors for SARS‐CoV‐2 RAST. A cross‐sectional study was conducted from April 21 to 30, 2022 in China. The χ 2 test and multivariate logistic regressions were used to identify the influencing factors. The structural equation model was used to test the extended protective motivation theory (PMT) model hypotheses. Among the total of 5107 participants, 62.5% were willing to accept the SARS‐CoV‐2 RAST. There were significant differences in acceptance among different residences ( p  < 0.001), educational level ( p  < 0.001), occupation ( p  < 0.001), monthly income ( p  < 0.001), travel frequency ( p  < 0.05), and feelings about NATT ( p  < 0.001). Response efficacy ( β  = 0.05; p  = 0.025) and self‐efficacy ( β  = 0.84; p  < 0.001) had a positive effect, while response cost showed a negative effect ( β  = −0.07; p  < 0.001). The public's major concerns about SARS‐CoV‐2 RAST are its reliability, testing method, price, and authority. Overall, a moderate intention to use SARS‐CoV‐2 RAST was found among the Chinese population. The extended PMT can be used for the prediction of intention to accept the RAST. We need to take measures to increase people's acceptance of SARS‐CoV‐2 RAST.